PROFESIONAL TRAINING OF FUTURE ENGINEERS AT TECHNICAL UNIVERSITIES AS A RELEVANT PEDAGOGICAL ISSUE - Алпатов, Сергій; Лузік, Ельвіра (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2025)
The article examines the professional training of future engineers at technical universities as a key pedagogical issue in today’s digital era. With rapid technological progress and digital transformation in education, the focus is on creating an effective educational and informational environment (EIE) that supports knowledge transfer, skill development, motivation for self-learning, critical thinking, and interdisciplinary collaboration. The aim of the study is to define pedagogical conditions for the effective training of engineers in a digital context. The research highlights the role of EIE in shaping professional competence, essential skills, and readiness for continuous learning. The study is based on systemic, competency-based, learner-centered, and activity-oriented approaches. It explores the theoretical foundations of EIE, its structure, functions, and didactic potential. The article also analyzes modern challenges in engineering education, conditions for competence development, and assessment methods. Results. The research shows how innovative technologies shape the educational environment of technical universities and points to prospects for further implementation. Key attention is given to the regulatory framework, blended learning, project-based activities, interactive methods, and LMS platforms. The development of engineer competence must take place in a digital space that actively integrates modern tools. The study concludes that effective engineer training requires a new understanding of the teacher’s role, digital environments, and educational models that support autonomy and lifelong learning.